2020
DOI: 10.1590/1984-0462/2020/38/2019017
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical Vector Analysis in Obese Adolescents

Abstract: Objective: To evaluate the hydration of obese and non-obese adolescents by vectorial bioimpedance analysis, in addition to verifying the associations between obesity and bioelectrical impedance vectorial analysis (BIVA) parameters. Methods: A cross-sectional study with adolescents between 14 and 18 years old (n=489, 300 boys and 189 girls). Electric bioimpedance (BIA; Quantum_II, RJL system, Rome, Italy) provided resistance and reactance parameters to calculate phase angle (PA), fat-free mass (FFM) and body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Another major issue is the differences in sex. In line with the fact that PhA is greater in male than female adults (1,5,17,31), a few studies have indicated that PhA was higher in male than female teenagers by around 7%-10% (1,2,14,22,24,32,37), with similar findings also in adolescent athletes (30,41), and only 1 exception (34). There is less consistent evidence for younger subjects (Table 1); in early adolescence, a slightly greater PhA was reported in males than females (2,24,25,32), while little or no significant differences emerged in children in 3 studies (1,2,35).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Another major issue is the differences in sex. In line with the fact that PhA is greater in male than female adults (1,5,17,31), a few studies have indicated that PhA was higher in male than female teenagers by around 7%-10% (1,2,14,22,24,32,37), with similar findings also in adolescent athletes (30,41), and only 1 exception (34). There is less consistent evidence for younger subjects (Table 1); in early adolescence, a slightly greater PhA was reported in males than females (2,24,25,32), while little or no significant differences emerged in children in 3 studies (1,2,35).…”
Section: Discussionmentioning
confidence: 88%
“…In children/adolescent pooled, 1 study (1) showed that PhA tended to increase with BMI in either sex, while another one (23) found similar values of PhA in participants with obesity compared to controls. PhA was also higher in participants with obesity compared to controls in both adolescents (37) and 8 years old children (35,36) (Table 1).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Studies reported that obese subjects had a higher PhA in comparison with eutrophic subjects (6.9 ± 0.9° vs. 6.5 ± 0.8°; p = 0.003) [ 17 ]. Table 1 summarizes data from a multicenter clinical study of 217 individuals, showing a decrease in PhA with respect to age in type 2 diabetes mellitus (T2D) subjects compared with the control group [ 18 ].…”
Section: Resultsmentioning
confidence: 99%